(111 8/11-2х)*89/110=32,873+<span>56,127
</span>(111 8/11-2х)*89/110=89 <span>
111 8/11-2х=89:89/110
</span>111 8/11-2х=89*110/89<span><span>
111 8/11-2х=110
2х=111 8/11-110
2х=1 8/11
х=19/11:2; х=38/11 или х=3 5/11</span></span>
Пусть х -скорость на спуске
тогда (х-2) -скорость на подъёме
6-4=2ч. -занял подъём
Составим уравнение
2(х-2)+4х=26
2х-4+4х=26
6х=26+4
6х=30
х=30:6
х=5 км/ч скорость туриста на спуске
20х+2(х-8)=20х+2х-16=22х-16
5а-2(2a-4)=5а-4а+8=а+8
80-(58+12)=10.................................
=5(0,9+0,6)-0,7(2+3)=5×1,5-0,7×5=5(1,5-5)=5×(-4,5)=-22,5